The neural correlates of regulating another person's emotions: an exploratory fMRI study - Hallam, Glyn P.; Webb, Thomas L.; Sheeran, Paschal; Miles, Eleanor; Niven, Karen; Wilkinson, Iain D.; Hunter, Michael D.; Woodruff, Peter W. R.; Totterdell, Peter; Farrow, Tom F. D. (Frontiers in Human Neuroscience, 2014)
Studies investigating the neurophysiological basis of intrapersonal emotion regulation (control of one’s own emotional experience) report that the frontal cortex exerts a modulatory effect on limbic structures such as the amygdala and insula. However, no imaging study to date has examined the neurophysiological processes involved in interpersonal emotion regulation, where the goal is explicitly to regulate another person’s emotion. Twenty healthy participants (10 male) underwent fMRI while regulating their own or another person’s emotions. Intrapersonal and interpersonal emotion regulation tasks recruited an overlapping network of brain regions including bilateral lateral frontal cortex, pre-supplementary motor area, and left temporo-parietal junction. Activations unique to the interpersonal condition suggest that both affective (emotional simulation) and cognitive (mentalizing) aspects of empathy may be involved in the process of interpersonal emotion regulation. These findings provide an initial insight into the neural correlates of regulating another person’s emotions and may be relevant to understanding mental health issues that involve problems with social interaction.